Reciprocal Signaling between Myeloid Derived Suppressor and Tumor Cells Enhances Cellular Motility and is Mediated by Structural Cues in the Microenvironment. Issue 6 (18th May 2020) - Shukla, Vasudha C.; Duarte‐Sanmiguel, Silvia; Panic, Ana; Senthilvelan, Abirami; Moore, Jordan; Bobba, Christopher; Benner, Brooke; Carson, William E.; Ghadiali, Samir N.; Gallego‐Perez, Daniel
Abstract: Myeloid derived suppressor cells (MDSCs) have gained significant attention for their immunosuppressive role in cancer and their ability to contribute to tumor progression and metastasis. Understanding the role of MDSCs in driving cancer cell migration, a process fundamental to metastasis, is essential to fully comprehend and target MDSC‐tumor cell interactions. This study employs microfabricated platforms, which simulate the structural cues present in the tumor microenvironment (TME) to elucidate the effects of MDSCs on the migratory phenotype of cancer cells at the single cell level. The results indicate that the presence of MDSCs enhances the motility of cancer‐epithelial cells when directional cues (either topographical or spatial) are present. This behavior appears to be independent of cell–cell contact and driven by soluble byproducts from heterotypic interactions between MDSCs and cancer cells. Moreover, MDSC cell‐motility is also impacted by the presence of cancer cells and the cancer cell secretome in the presence of directional cues. Epithelial dedifferentiation is the likely mechanism for changes in cancer cell motility in response to MDSCs. These results highlight the biochemical and biostructural conditions under which MDSCs can support cancer cell migration, and could therefore provide new avenues of research and therapy aimed at stemming cancer progression. Abstract : This study explores the reciprocal interaction between the myeloid derived suppressor cells (MDSCs) and cancer cells, mediated by structural/directional cues from the environment, leading to enhanced migration not only in cancer cells but also in MDSCs. It combines biomimetic platforms with one of the major players of cancer immunology to uncover synergies that could potentially contribute to disease progression .